Peranan Gaya Kepemimpinan dan Budaya Organisasi Dalam Meningkatkan Semangat Kerja Karyawan Pada PT. Angkasa Pura Supports Head Office Kemayoran Jakarta Pusat - Ahmad Juhari; Zubair Zubair (Peneliti.net, 2022)
Leadership style is the behavior used by a leader when influencing others in doing a job to achieve certain goals. Leadership behavior displayed by a leader if it feels good and pleases employees, it will influence and have a better impact on employee morale. Likewise with the organizational culture which is very influential on the morale of employees in carrying out their work. Conversely, if the behavior displayed by a leader is something that is not in accordance with the expectations of employees, it will not be good for the morale of the employees themselves. The purpose of this study was to analyze how influential the role of leadership style and organizational culture in increasing employee morale at PT. Angkasa Pura Supports Head Office Kemayoran Central Jakarta. This study uses a qualitative method with in-depth and structured interviews. The informants taken were Key Informants from the Unit Head and 4 informants as employees of PT. Angkasa Pura Supports. The data collection technique uses a data credibility test from the results of interviews. the implementation of organizational culture is uneven, resulting in some employees not implementing it and still low employee morale, which is caused by a leadership style that influences employee performance.